Location of Aryl Sulfatase in Conidia and Young Mycelia of Neurospora crassa - Scott, Walter A. (1970)
Aryl sulfatase (arylsulfate sulfohydrolase, EC 3.1.6.1) was found to have multiple locations in Neurospora conidia. Some enzyme activity remained in the supernatant when a spore suspension was centrifuged or filtered. Part of the cell-bound activity could be detected by adding the assay ingredients to a suspension of intact spores (patent enzyme), and additional activity was only detectable when the spores were first treated to destroy their permeability barriers (cryptic enzyme). Such treatments include: disruption with an X-press, brief rinsing with chloroform or acetone, incubation at 60 C for 5 min, and incubation with phenethyl alcohol, nystatin, or ascosin. Part of the patent aryl sulfatase was inactivated by briefly acid treating the intact spores (no loss of conidial viability). This enzyme was considered to have a cell surface location. Some enzyme was acid-resistant in intact spores, but all of the enzyme was acid-sensitive in spores whose permeability barriers had been disrupted. The pH dependence, kinetic properties, and p-nitrophenyl sulfate uptake were investigated in acid-treated conidia. No aryl sulfatase was detected in ascospores. Young mycelia contained more aryl sulfatase than did conidia, but little, if any, was secreted into the growth medium. Cryptic activity was demonstrated in young mycelia by brief chloroform treatment or by rinsing the cells with 0.1 m acetate buffer. Enzyme activity in young mycelia was completely labile to acid treatment, as was cell viability.